2018
DOI: 10.1080/09168451.2018.1460573
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the 7S and 11S globulins as percutaneously sensitizing soybean allergens as demonstrated through epidermal application of crude soybean extract

Abstract: Cutaneous exposure to food allergens can predispose individuals to food allergies. Soybean, a major allergenic food, is an ingredient in various cosmetic products. However, the types of soybean proteins that are percutaneously sensitizing in humans or animal models remain unknown. In this study, BALB/c mice were dorsally shaved and epicutaneously exposed to a crude soybean extract including sodium dodecyl sulfate or distilled water alone. Specific IgEs secreted in response to 7S globulin (Gly m 5), 11S globuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Previously, we identified that principal soybean allergens Gly m 5 and Gly m 6 trigger percutaneous sensitization in a mouse model (9). Using the same model, the soybean trypsin inhibitor Gly m TI was also identified as a soybean allergen that causes percutaneous sensitization (10).…”
Section: Popular Scientific Summarymentioning
confidence: 90%
“…Previously, we identified that principal soybean allergens Gly m 5 and Gly m 6 trigger percutaneous sensitization in a mouse model (9). Using the same model, the soybean trypsin inhibitor Gly m TI was also identified as a soybean allergen that causes percutaneous sensitization (10).…”
Section: Popular Scientific Summarymentioning
confidence: 90%
“…Simultaneously, soybean is also one of the "eight major allergens" that identified by the FAO [127]. Studies have shown that with the increase in the use of soybean and soybean products, about 1-6% of infants and children are allergic to soybean and the incidence of soybean allergies in adults is also increasing [128,129]. There are 11 kinds of allergenic proteins found in soybeans, namely: β-conglycinin (Gly m 5), hydrophobic protein, defensive protein, inhibitory protein, SAM22, 7S globulin, glycinin (Gly m 6), 2S albumin, lectin, lipoxidase, and trypsin inhibitor [130][131][132].…”
Section: Soybeanmentioning
confidence: 99%
“…Recently, some global regulatory agencies started requiring quantitative analysis of individual allergens, including unproven allergens, as part of the risk assessment for genetically engineered soy beans [38]. Identification of allergenic globulins as percutaneously sensitized soybean allergens have been demonstrated through epidermal application of crude soybean extract [39]. Glycinin and β-conglycinin can induce intestinal damage [40].…”
Section: Recent Advances In the Control Of Allergic Reaction To Soybeanmentioning
confidence: 99%